Lifestyle Behaviours among General Population During Lockdown Period during Corona Virus Disease-19 Pandemic - Shrestha, Marina Vaidya; Shrestha, Sunil Babu; Manandhar, Naresh; Joshi, Sunil Kumar (Journal of Nepal Health Research Council, 2022)
Background: Healthy lifestyle behaviours have been consistently associated with reduced non-communicable disease related morbidity, mortality and wellbeing. Unhealthy behaviours are major contributors to the global burden of disease. The main aim of this study is to access lifestyle behaviours in adults during the corona virus disease-19 pandemic. Methods: Cross sectional study was conducted among general population residing in Nepal. Online questionnaire was developed using Google Forms. Questionnaire comprised of three validated tools regarding the following lifestyle behaviours: Physical activity, Nutrition, Sleep. The collected data was analysed using SPSS version 20. To test the differences between changes in dietary and physical activity behaviours in relation to changes in body weight a Chi-square test was used. Results: During Covid -19 lockdown, 124(42%) participants performed moderate level of physical activity. Of those participated, 127(43.1%) and 44(14.9%) reported an increase and decrease of weight, respectively. Among 110(37.3%) who reported snacking in lockdown led to weight gain in 68(61.8%). Availability of more time for meal preparation (24.1%) and feelings of boredom (17.4%) were the main reasons for changing dietary habits. The subjective sleep quality of participants was as follows: very good-40.3%; fairly good-45.4 %; fairly bad-11.2%; very bad 3.1%. There was significant positive correlation between sleep quality and sleep duration (R=0.261; P<0.001), sleep latency (R=0.362; P<0.001), sleeping medications (R=0.174; P<0.003) and daytime dysfunction (R=0.308; P<0.001). Conclusions: Life style behaviours were affected during lockdown period. Higher amounts of food intake and snaking were increased. Physical activity was at a moderate level, increased sedentary behaviour was reported by most participants during lockdown. However, sleep quality was not negatively affected. Keywords: Corona virus disease-19; diet; lockdown; lifestyle behaviour; physical activity.